Loyalitas Merek Pada Jasa Penerbangan: Suatu Studi Empiris - Kevin Susanto; Hansel Ferdinand; Revel Gunawan; Sabrina O Sihombing (Faculty of Economic and Business, 2018)
Brand Loyalty on Airline Services: An Empirical StudyConsumer loyalty is an important element for the sustainability of a business. Therefore, an understanding of the key factors determining loyalty is important. In relation to aviation services, particularly AirAsia, several events that have occurred in AirAsia may affect consumer loyalty to the airline. Therefore, this study aims to examine the relationship between variables, especially variables affecting brand loyalty such as customer identification of the brand, service quality, perceived value, and brand trust. Data collection method in this research is non-probability sampling method. Questionnaires were distributed to 175 respondents. The results of the questionnaire obtained were studied using Structural Equation Modeling (SEM). The results show that only perceived values ​​has no significant relationship with loyalty.DOI: 10.15408/ess.v8i1.5553